Introduction - Croissant, Aurel; Kühn, David (Reforming Civil-Military Relations in New Democracies, 2017)
Political scientists studying civil-military relations have always been particularly concerned with the “civil-military problematique” (Feaver): how to create and preserve a military that is subordinate to the authority of political leaders but strong enough to fulfill its functions? Most of the scholarly literature on civil-military relations in democratic transformations focuses on the subordination of the armed forces to civilian authority and whether new democracies can succeed in preventing their armed forces from overthrowing democracy. At the same time, however, other and often more relevant reform issues tend to be overlooked. In fact, while it seems that contemporary democracies are quite successful in proofing themselves against military coups and other forms of direct or indirect military incursions, as the remarkable and steady decline of coup d’états and military regimes since the mid-1980s indicate, many have been considerably less successful in establishing civilian supremacy over national defense and military policy-making. This is true not only for most of the former military-ruled countries of Latin America, Southern Europe, Asia, and Africa, but also of post-communist countries in Europe and the former Soviet Union. Moreover, besides the demilitarization of defense policy-making, the effectiveness of the armed forces in fulfilling their assigned roles and missions also often remains problematic. In fact, many new democracies are not well prepared to develop strong institutions for the democratic control of the armed forces and turning them into effective providers of security and protection.